Exostoses and compression of supraepitrochlear median nerve, at the elbow - Quagliotto, Evasio (Cirugía del Uruguay, 1974)
Brachialgic and cervico-brachialgic disorders are a frequent complaint of our times and consequently this case of supraepitrochlear exostosis with functional manifestations which indicate involvement of median nerve, possibly the first such case to be reported in Uruguay, may prove to be of interest. Exostosis and anomalies in concomitant soft parts, as well as manifestations of median nerve involvement of sensitive type, coincided with findings in ali cases in available bibliography. Treatment followed the rules advocated sincel 1938; postoperotory evolution resulted in the partients functional, biological and morphological recovery. Since supraepitrochlear exostosis may affect not only the median nerve but also other noble structures in the vicinity, surgical treatment is justified.